Pengaruh Ekstrak Etanol Daun Sirsak (Annona Muricata L.) Terhadap Kadar LDL Pada Mencit Putih Jantan - Surya Dharma; Oki Supanda; Elisma Elisma (Jurnal Farmasi Higea, 2014)
Study about the influence of the aethanolic extract of Annona muricata L on male mice induced by high fat diet and propylthiouracil has been done. The aethanolic extract of Annona muricata L was given orally one a day for 7, 14, and 21 days. The doses used were 2, 6, 18 mg/20 g body weight respectively. Negative control group was given standard food. Parameters were measured blood levels of LDL. Result showed that the giving of the aethonalic extract of Annona muricata could decrease blood levels of LDL significantly (p> 0.05). Whereas the factors of the days does not show significantly (p> 0.05).